Agro-Ecological Sub-region: A wheel of technology transfer for crop planning - Mandal, C.; Bhattacharyya, T.; Venugopalan, M. V.; Tiwary, P.; Pal, D. K. (Indian Farming, 2015)
In the present study all the information which made the backbone of soil information system has been utilized for generating maps for cotton and soybean crops in BSR and rice and wheat in the IGP to find out various soil factors controlling their performance. For example, in the IGP the selected AESRs represented by the dominant soils producing <1000 and 1000-2500 kg/ha yield of rice and wheat have soil related constraints which can be rectified following management interventions. These interventions might push the AESRs with low to medium yield to medium high to high yield. And thus show the importance of soil information vis-avis AESRs in crop planning and management.